Establishment, characterization, and drug screening of low-passage patient individual non-small cell lung cancer in vitro models including the rare pleomorphic subentity - Andus, Ingo; Prall, Friedrich; Linnebacher, Michael; Linnebacher, Christina S. (Frontiers in Oncology, 2023)
Introduction For pre-clinical drug development and precision oncology research, robust cancer cell models are essential. Patient-derived models in low passages retain more genetic and phenotypic characteristics of their original tumors than conventional cancer cell lines. Subentity, individual genetics, and heterogeneity greatly influence drug sensitivity and clinical outcome. Materials and methods Here, we report on the establishment and characterization of three patient-derived cell lines (PDCs) of different subentities of non-small cell lung cancer (NSCLC): adeno-, squamous cell, and pleomorphic carcinoma. The in-depth characterization of our PDCs included phenotype, proliferation, surface protein expression, invasion, and migration behavior as well as whole-exome and RNA sequencing. Additionally, in vitro drug sensitivity towards standard-of-care chemotherapeutic regimens was evaluated. Results The pathological and molecular properties of the patients’ tumors were preserved in the PDC models HROLu22, HROLu55, and HROBML01. All cell lines expressed HLA I, while none were positive for HLA II. The epithelial cell marker CD326 and the lung tumor markers CCDC59, LYPD3, and DSG3 were also detected. The most frequently mutated genes included TP53, MXRA5, MUC16, and MUC19. Among the most overexpressed genes in tumor cells compared to normal tissue were the transcription factors HOXB9, SIM2, ZIC5, SP8, TFAP2A, FOXE1, HOXB13, and SALL4; the cancer testis antigen CT83; and the cytokine IL23A. The most downregulated genes on the RNA level encode the long non-coding RNA LANCL1-AS1, LINC00670, BANCR, and LOC100652999; the regulator of angiogenesis ANGPT4; the signaling molecules PLA2G1B and RS1; and the immune modulator SFTPD. Furthermore, neither pre-existing therapy resistances nor drug antagonistic effects could be observed. Conclusion In summary, we successfully established three novel NSCLC PDC models from an adeno-, a squamous cell, and a pleomorphic carcinoma. Of note, NSCLC cell models of the pleomorphic subentity are very rare. The detailed characterization including molecular, morphological, and drug-sensitivity profiling makes these models valuable pre-clinical tools for drug development applications and research on precision cancer therapy. The pleomorphic model additionally enables research on a functional and cell-based level of this rare NCSLC subentity.